Insight in structures of superbulky metallocenes with the Cp BIG ligand: Theoretical considerations of decaphenyl metallocenes - Kuchenbecker, Dennis; Harder, Sjoerd; Jansen, Georg (Zeitschrift für Anorganische und Allgemeine Chemie, 2010)
The structures of a series of decaphenyl metallocenes (Ph Cp)M, which model superbulky metallocenes, are calculated by means of density functional theory including a semi-empirical correction for dispersion interactions (DFT+D). Through a detailed investigation of the calcocene it is shown that the interactions between the phenyl substituents of the two cyclopentadienyl ligands lead to a preference of S10 symmetrical structures and that dispersion interactions contribute to the overall stability of superbulky metallocenes. Whereas the Ph substituents of the two ligands bend away from each other with standard DFT, inclusion of the dispersion correction reproduces the experimentally observed slight inclination towards each other. The experimentally observed linear correlation between the out-of-plane bending angle of the phenyl substituents and the size of the metal atom M (M = Fe, Ni, Cr, W, Ca, Yb, Sn, Sm, Sr, Ba) is also confirmed at the DFT+D level. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.